Effective gravitational equations for f(R) braneworld models - Caramês, T. R P; Guimarães, M. E X; Hoff Da Silva, J. M. [UNESP] (American Physical Society (APS), 2013)
The viability of achieving gravitational consistent braneworld models in the framework of a f(R) theory of gravity is investigated. After a careful generalization of the usual junction conditions encompassing the embedding of the 3-brane into a f(R) bulk, we provide a prescription giving the necessary constraints in order to implement the projected second-order effective field equations on the brane. © 2013 American Physical Society.